Research on 5G communication architecture of distribution network and its latency with reliability - WANG Haiyang; WANG Yudong; LIU Han; SUN Haipeng; YANG Jin; LI Zhenghao (Dianxin kexue)
The core value of 5G in the field of digital distribution network is to give play to the technical advantages of 5G in ultra-high reliability and low latency, and provide high reliability and low latency communication for the control related business of distribution network. In order to provide a systematic theoretical analysis scheme for the latency and reliability of 5G communication deployment applications in the distribution network, a typical architecture of 5G communication in the distribution network in combination with digital distribution network services was given, the latency model for 5G communication in the distribution network was deeply analyzed. The end-to-end latency analysis for 5G frame structures of four operators in China was conducted with 5G reliability values of 3GPP Rel-15 and Rel-16 through 5G link level simulation. At last, a joint analysis method of time latency and reliability of 5G communication in distribution network was proposed.